Comparison Between End-to-end Anastomosis and Buccal Mucosa Graft in Short Segment Bulbar Urethral Stricture: a Meta-analysis Study - Prahara Yuri; Irfan Wahyudi; Arry Rodjani (Acta Medica Indonesiana, 2016)
Aim: to compare long term follow-up between end-to-end urethroplasty and bucal mucosal graft for the management of patients with short bulbar urethral stricture. Methods:we conducted a meta-analysis of cohort studies. Literature research was performed on the MEDLINE, Science Direct, and EMBASE database including studies from 1980 through 2014. The inclusion criteria were patients with short bulbar urethral strictrure (sized ≤3 cm) undergoing end-to-end anastomosis (EE) and buccal mucosa graft (BMG) with the complication of voiding symptoms and sexual dysfunction ≥12 months. Pooled risk ratio (RRs) and 95% confidence interval (CIs) were calculated using Mantzel-Haenzel method, while the heterogeneity were determined through I2 value. Data analysis were done using Stata software version 10.0 (StataCorp). Results:We analyze 10 studies in this meta-analysis. Sexual dysfunction following EE and BMG were found in 24.6% (45/183) patients and 9.1% (11/122) patients, respectively (overall RR 2.54; 95% CI: 1,44-4,47; p=0.001). Voiding symptoms following EE and BMG were found in 14% (8/57) patients and 12.5% (7/56) patients, respectively (overall RR 0.77; 95% CI: 0.3–2.0; p=0.591). Furthermore, stricture recurrent following EE and BMG were 8.4% (8/107) and 30% (14/46), respectively (overall RR 0.38; 95% CI: 0.17–0.84; p=0.016). The effectiveness of EE and BMG were found to be equal as both demonstrated few complications. BMG were found to be superior than EE terms of minimal sexual dysfunction complication. On the contrary, EE were found to be superior than BMG in terms of stricture recurence following short bulbar urethral stricture surgery. Conclusion:BMG can be considered as the primary treatment rather than EE for managing short urethral stricture cases.